Oxaloacetate enhances and accelerates regeneration in young mice by promoting proliferation and mineralization - Jaramillo, Josue; Taylor, Caroline; McCarley, Rachel; Berger, Melissa; Busse, Emily; Sammarco, Mimi C. (Frontiers in Cell and Developmental Biology, 2023)
Cell metabolism coordinates the biochemical reactions that produce carbon and ATP in order for the cell to proliferate, differentiate, and respond to environmental changes. Cell type determines metabolic demand, so proliferating skeletal progenitors and differentiated osteoblasts exhibit different levels of cell metabolism. Limb regeneration is an energetically demanding process that involves multiple types of tissues and cell functions over time. Dysregulation of cell metabolism in aged mice results in impaired regeneration, a defect that can be rescued in part by the administration of oxaloacetate (OAA). A better understanding of how cell metabolism regulates regeneration in general, and how these changes can be modulated to benefit potential regenerative strategies in the future is needed. Here we sought to better understand the effects of OAA on young mice and determine whether the same mechanism could be tapped to improve regeneration without an aged-defect. We also asked which dosing time periods were most impactful for promoting regenerative outcomes, and whether these effects were sustained after dosing was stopped. Consistent with our findings in aged mice we found that OAA enhanced regeneration, even beyond control measures, by increasing trabecular thickness, decreasing trabecular spacing, and improving the patterning by decreasing the taper, making the regenerated bone more like an unamputated digit. Our data suggests that the decrease in spacing, an improvement over aged mice, may be due to a decrease in hypoxia-driven vasculature. Our findings suggest that OAA, and similar metabolites, may be a strong tool to promote regenerative strategies and investigate the mechanisms that link cell metabolism and regeneration.